THE RELATIONSHIP BETWEEN FOOT SOAKING THERAPY WITH WARM WATER AND RESPIRATORY RELAXATION TECHNIQUES ON LOWERING BLOOD PRESSURE IN HYPERTENSIVE PATIENTS IN SUDIANG RAYA VILLAGE - Hasliani (AKADEMI TEKNIK ADI KARYA, 2025)
Hypertension is a condition often referred to as a silent killer because many people are unaware that they have it, which can ultimately lead to very serious consequences. The high number of people with hypertension contributes to an increase in mortality and the risk of complications from year to year. This study aims to evaluate the effectiveness of a combination treatment of warm foot baths and deep breathing relaxation techniques in lowering blood pressure among hypertensive patients in Sudiang Raya Village, Makassar City. This study was conducted using a quasi-experimental method and a post-test group design. The study was conducted in Sudiang Raya Village. There were 19 respondents involved in this study, with sampling conducted using purposive sampling. The results of non-parametric analysis using the Wilcoxon test showed a p-value of 0.001